The Role of Scholarships in Improving Access to Education in Private Schools - H. Soro , Suharyanto; Hasan J, Muhamad; Ailya, Ashima (Civiliza Publishing, Indonesia., 2025)
This research is motivated by the fact that many students from financially disadvantaged families still have difficulty accessing education in private schools. Scholarships are believed to be one of the strategic solutions to increase access to education that is more equitable and inclusive. The purpose of this study is to find and analyze the role of scholarship programs in increasing access to education in private schools, especially in the Al-Masthuriyah Sukabumi Formal Diniyah Education (PDF). This study uses a case study approach. Data collection methods include observation, in-depth interviews, and documentation studies. The results of the study indicate that there is no official SOP regarding the scholarship program at PDF Al-Masthuriyah. The implementation of scholarship assistance is carried out internally (including free tuition, dispensation, and cash) has been carried out based on certain criteria such as economic conditions and student achievement. The scholarship program has been proven to be able to help students from disadvantaged families to continue their education, increase learning motivation, and reduce dropout rates. In conclusion, with proper planning, implementation, evaluation, and follow-up, scholarships are not only a financial aid tool, but also an effective instrument for equalizing education.